Rekayasa Bahan untuk Meningkatkan Daya Serap Terhadap Gelombang Elektromagnetik dengan Matode Deposisi Menggunakan Lucutan Korona - Gunawan S.K., Vincensius (BERKALA FISIKA, 2006)
The aim of this research is to engineer soft steel  which have low value absorbance of electromagnetic waves become  a material which have higher value absorbance.  The method used is deposition by corona discharge. Corona discharge generated in free space will ionisize air producing nitrogen ion that can be deposite in basic material.  This process will increase the density in the surface of basic materials and then will make the value of linear absorbance constant of basic material become higher.  The optimal result in this research is the raise of  the value of linear absorbance constant by 54,3 % with the time of deposition in 30 minutes, the voltage of electrode 5 kV and  distance between electrodes 6 mm.